Openness and Urban Governance: How Transparency Erodes Local Government - Frans Jorna (Central European Public Administration Review)
Local government political leaders have a hard job these days. More and more they are confronted by citizens demanding transparency and a say in the production of social goods. Challenging the hegemony of local government, they connect their resources to come up with grass roots solutions. Fear of litigation claims and an increase in the complexity of policymaking and administration and fiscal scarcity render local administrations risk averse. How to effectively structure the frontline between local government and local communities? Open and collaborative governance approaches hold the promise of developing to mediate these tensions, but what are the implications for the way local democracy, local government and local administration work? This article looks at the ugly face of trust in collaborative and open governance on the basis of a comparative casestudy from Apeldoorn (The Netherlands). The article identifies and analyses patterns of (a lack of) open governance and offers alternative models to the organization of the frontline between local government and society.